About the identity of Tagetes pauciloba (Asteraceae, Tageteae) - Schiavinato, Dario J.; Bartoli, Adriana (Phytotaxa, 2018)
Tagetes pauciloba, a species previously included in the synonymy of T. filifolia, is reinstated as a distinct species, and T. mendocina is placed in the synonymy of T. pauciloba. An epitype of T. pauciloba is designated. A revised morphological description of T. pauciloba is presented, including the presence of gemmiferous roots noted for the first time in Argentinian species of Tagetes. Distribution of T. pauciloba and T. filifolia in Argentina is mapped. A key to distinguish T. pauciloba from its Argentinian congeners with perennial habit is provided.